Sociology of legal images - Mulcahy, L (Edward Elgar Publishing, 2020)
Law’s relationship to images has often been assumed or ignored but until recently there have been few attempts to unravel the law-image dynamic. Representations of law and legal phenomena in a range of forms including sculpture, fine art, film, cartoons and street art play a critical role in constructing and re-constructing ideological hegemony and myths about law through the creation of a set of permitted symbols. The challenge for socio-legal scholars is to understand and interrogate these visual codes, interrogate how they wield power and to plot the ways in which they are experienced on a day to day basis.